Exploring intercultural learning through a blended course about open education practices across the Mediterranean - Nascimbeni, Fabio; Burgos, Daniel; Aceto, Stefania; Wimpenny, Katherine; Maya, Isidro; Stefanelli, Cristina (IEEE Global Engineering Education Conference, EDUCON, 2020)
This paper presents and reflects upon the training course organized by the OpenMed project, aimed at building capacity in Open Educational Resources (OER) and Open Education approaches across universities from the South Mediterranean, namely in Egypt, Jordan, Lebanon, Morocco and Palestine. The course, which is currently being piloted among 10 universities, represents an example of an intercultural and multilingual learning experience, both from the way in which it was conceived and developed, to the way it is actually being delivered. In this paper, we reflect on the challenges and benefits of adopting such an open approach towards intercultural learning.
Ponencia de la conferencia "Volume 2018-April, 23 May 2018, Pages 285-288 2018 IEEE Global Engineering Education Conference - Emerging Trends and Challenges of Engineering Education, EDUCON 2018; Santa Cruz de Tenerife, Canary Islands; Spain; 17 April 2018 through 20 April 2018"
Keywords: blended learning; intercultural learning; Mediterranean region; open education; open educational resources; Scopus(2)